A Formative Assessment Tool for Conceptual Database Design Using UML Class Diagram - Soler, Josep; Boada, Imma; Prados, Ferran; Poch, Jordi; Fabregat, Ramon (International Journal of Emerging Technologies in Learning (iJET), 2010)
Database design is one of the main topics of any introductory database course. Traditionally, for teaching it entity-relationship diagrams (ERD) are used. However, in the last years, Unified Modeling Language (UML) has emerged as an effective modeling tool for database design. In this paper we present a web-based tool designed to give support to teaching and learning conceptual database design using UML class diagrams. The proposed UML environment is an effective tool for formative assessment since it is capable of correcting automatically UML class diagrams exercises providing immediate feedback to the student. The tool is part of a more general framework, denoted ACME, which provides the main functionalities of an e-learning platform. The tool has been used in a first experimental group of an introductory database course